2020
DOI: 10.1044/2020_aja-20-00018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Auditory, Language, Memory, and Attention Abilities in Children With and Without Listening Difficulties

Abstract: Objectives School-age children with and without parent-reported listening difficulties (LiD) were compared on auditory processing, language, memory, and attention abilities. The objective was to extend what is known so far in the literature about children with LiD by using multiple measures and selective novel measures across the above areas. Design Twenty-six children who were reported by their parents as having LiD and 26 age-matched typically develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Building on this idea, the relationship between language measures and working memory capacity has been well-documented in normal- and hard-of-hearing adults ( Akeroyd, 2008 , Besser et al, 2013 , Gordon-Salant and Cole, 2016 , Hwang et al, 2017 ) and children ( Dawson et al, 2002 , Harris et al, 2013 , Kirby et al, 2019 , Lowenstein et al, 2019 , Magimairaj and Nagaraj, 2018 , Magimairaj et al, 2018 , Magimairaj et al, 2020 , McCreery et al, 2017 , McCreery et al, 2019 , Nittrouer et al, 2017 ). In the context of children with mild-to-severe hearing loss, Stiles and colleagues ( Stiles et al, 2012 ) found a significant relationship between digit span and vocabulary size in both CNH and CHL.…”
Section: Introductionmentioning
confidence: 99%
“…Building on this idea, the relationship between language measures and working memory capacity has been well-documented in normal- and hard-of-hearing adults ( Akeroyd, 2008 , Besser et al, 2013 , Gordon-Salant and Cole, 2016 , Hwang et al, 2017 ) and children ( Dawson et al, 2002 , Harris et al, 2013 , Kirby et al, 2019 , Lowenstein et al, 2019 , Magimairaj and Nagaraj, 2018 , Magimairaj et al, 2018 , Magimairaj et al, 2020 , McCreery et al, 2017 , McCreery et al, 2019 , Nittrouer et al, 2017 ). In the context of children with mild-to-severe hearing loss, Stiles and colleagues ( Stiles et al, 2012 ) found a significant relationship between digit span and vocabulary size in both CNH and CHL.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Moore et al (2010) and Snowling et al (2018) we predicted that tone-perception tasks would not contribute unique variance to narrative comprehension. However, we also predicted that SPiN would significantly contribute uniquely to narrative comprehension in children with DLD (Torkildsen et al, 2019;Magimairaj et al, 2020).…”
Section: The Current Studymentioning
confidence: 85%
“…Children are particularly vulnerable to the effects of noise on spoken communication, and this is exacerbated for children with DLD, attention deficits, and hearing loss. In a recent study, along with poor SPiN scores, children with reported listening difficulties scored lower on STM capacity, sentence recall, inferencing ability, and reduced speed and accuracy of lexical access, compared to a control group (Magimairaj et al, 2020). Furthermore, found that lexical knowledge was crucial for auditory closure of words and sentences in children, with lexical retrieval from LTM significantly associated with the recognizing interrupted sentences.…”
Section: Implications Of Listening Difficulties In Noisementioning
confidence: 93%
See 2 more Smart Citations